Climate Change, Desertification, and Water Stress in Kalmykia - Holland, Edward C.; Churyumova, Elvira (DEU, 2023)
In Russia as a whole, climate change has led to higher temperatures, permafrost thawing, human health impacts due to extreme heat, and higher incidence of forest fires and other natural disasters, among other country-wide consequences. Warming associated with a changing climate is best viewed as a risk multiplier that will exacerbate existing environmental stresses in locally nuanced ways. The most significant impacts of climate change in the Republic of Kalmykia, located in Russia's southwest, are distinct from those visible nationally and include desertification and increased pressure on an already low-quality water supply.